Kajian Penerapan Metode Horizontal Directional Drilling (HDD) untuk Pemasangan Pipa HDPE diameter 700 mm pada Crossing Pipa Gas di Jalan Syakyakirti, Kelurahan Karang Jaya, Kota Palembang - Marlinda, Marlinda; K.M. Aminuddin; Juliana, Imroatul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Underground pipe installation in urban areas faces various challenges, especially in avoiding existing infrastructure such as gas pipes and underground cables. The Horizontal Directional Drilling (HDD) method is an effective solution to reduce disturbance to the surrounding environment. This study examines the application of the HDD method in the installation of 700 mm diameter HDPE pipes at gas pipe intersections on Jalan Syakyakirti, Karang Jaya Village, Palembang City. This study was conducted by analyzing the implementation method, success factors, and risk mitigation applied during the drilling and pipe installation process. This research method includes a geotechnical survey to determine soil characteristics, selection of tools such as Pilot Bore Sensors to monitor drilling paths, and the use of the right slurry mix to maintain borehole stability. The HDD implementation process consists of several main stages, namely pilot drilling, widening the borehole using a back reamer, and pulling the pipe (pullback process) with a controlled technique to prevent pipe stoppage or failure. The safe distance between the existing gas pipeline and the HDD line is maintained within 5–7 meters to reduce potential risks. The results showed that the HDD method was successfully implemented, with a high level of accuracy in maintaining the drilling position and direction. The use of the right slurry mix has been shown to reduce efficiency and increase the efficiency of the drilling process. In addition, constant pullback speed control is a key factor in preventing HDPE pipe stoppages during installation. This study concludes that the HDD method is a safe and efficient technique for pipe installation in areas with limited space and the presence of underground infrastructure.